The Comparison of Jokowi and Prabowo Subianto Exposed on YouTube - Redi Panuju (Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
This article reviews the exposure ratio of Jokowi and Prabowo in the YouTube channel. Joko Widodo’s alias, Jokowi, is the President of the Republic of Indonesia 2014-2019. He will re-join the 2019 presidential election, while Prabowo Subianto is a challenger who is supported by the Gerindra Party and the Prosperous Prosperity Party. The analytical method uses the semiotic concept of Strauss and John Fiske, who view the video as a sign system. The sign system is parsed through five political codes: lifestyle, transfer of power, existence, ideology and vision. This study finds that, in general, Jokowi's videos were more visited and preferred than Prabowo's videos, but Prabowo excelled in the transfer code of power, existence and ideology. In the video, Jokowi tends to impress himself as a person who has several characters. As the President of Indonesia, Jokowi displays a diligent character. As a political activist, Jokowi reinforces his ideology as a nationalist. As a citizen, Jokowi imitates the figure who adheres to the values of tradition As a man, Jokowi impressed himself as a humanist. Prabowo tends to feature a lavish lifestyle with equestrian sport with a historical background of the descendants of an economic Democrat Prof Sumitro Djojohadikusumo and associates himself like Soekarno. Prabowo tends to show his affiliation to the right Islamists. The contestation of the 2019 presidential election followed by Jokowi and Prabowo will show the battle of two different sources of legitimacy.